2003
DOI: 10.1016/s0029-7844(03)00862-7
|View full text |Cite
|
Sign up to set email alerts
|

Folic Acid Awareness in Michigan, 1996–1999

Abstract: Although folic acid awareness has increased among Michigan mothers overall during 1996-1999, it has decreased among women with less than a high school education, and substantial gaps exist among socioeconomic subgroups. Continued efforts are needed to improve folic acid awareness and consumption of folic acid among women of reproductive age, with special attention focused on populations experiencing gaps or declines in folic acid awareness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…The very low % of women in our study who knew about fetal effect and appropriate time of supplementation in relation to pregnancy (16.3% and 5.0% respectively) was lower than the Chinese study (30% and 23% (Ren et al, 2006)) but comparable to the study from India (Gupta, 2000), where no women demonstrated knowledge of these facts. Our findings that being under the age of 25 and having less education were associated with lower awareness are consistent with results published in previous studies that included these co-variates (Abdulrazzaq et al, 2003;Alozie Arole et al, 2003;Canfield et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
“…The very low % of women in our study who knew about fetal effect and appropriate time of supplementation in relation to pregnancy (16.3% and 5.0% respectively) was lower than the Chinese study (30% and 23% (Ren et al, 2006)) but comparable to the study from India (Gupta, 2000), where no women demonstrated knowledge of these facts. Our findings that being under the age of 25 and having less education were associated with lower awareness are consistent with results published in previous studies that included these co-variates (Abdulrazzaq et al, 2003;Alozie Arole et al, 2003;Canfield et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
“…hearing or reading about folic acid 3,14,15,17,[26][27][28][29][30][31][32][33][34] ; knowledge, as having any information about the role of folic acid in prevention of neural tube defects or other congenital malformations 3,17,26,[29][30][31][33][34][35][36][37][38][39] ; and consumption, as periconceptional daily intake of folic acid (before and after conception). 3,17,18,26,27,29,30,35,40,41 The outcome measurements consisted of women's self-reported intakes.…”
Section: Resultsmentioning
confidence: 99%
“…To clarify missing data identified in six studies, we contacted the authors of these studies. [14][15][16][17][18][19]…”
Section: Data Sourcesmentioning
confidence: 99%
“…Several explanations may be responsible for these discrepant findings. For NTDs it has been postulated that the MTHFR 677CRT polymorphism may only be a risk factor in populations with poor folate nutrition (Shields et al, 1999;Botto and Yang, 2000;Arole et al, 2003), but under conditions of complete folate supply, potential association may be masked. Likewise, the MTHFR 677T risk allele may only play a role in the etiology of nonsyndromic CL/Ps under the conditions of overall folate deficiency.…”
Section: Discussionmentioning
confidence: 99%